(untitled) (Journal of Engineering Science, 2021)
This study aims at investigating the effect of meteorological parameters on seasonal variation of particulate matter(PM) (both PM2.5 and PM10) using a 4-year (2013-2016) monitoring data of air quality parameters from CASE project implemented by the Department of Environment (DoE). Using monthly data of the Continuous Air Monitoring Station(CAMS) of Darus-Salam, Dhaka, cross correlation analysisis performed between PM and meteorological parameters where inverse relationships of PM with temperature, rainfall and relative humidity are found. Increased biomass burning during low temperature period, washout effect of rainfall, wet deposition mechanism of higher humidity may be held responsible for these negative correlations. Significant seasonal variation is observed from daily data analysis of Darus Salam station and it is found that winter PM concentrations are 4.5-5.5 times higher than monsoon PM concentrations. Seasonal cross-correlation between PM10 and PM2.5 shows lower correlation during winter (December-February) and monsoon (June-September) seasons. Two possible effects can attribute to this seasonal difference: i) presence of biomass burning during winter which increases PM2.5 and ii) presence of rainfall during monsoon which decreases PM10.PM2.5/PM10 ratios for different months indicate the contrasting influences of different mechanisms on different sized PM particles. PM2.5/PM10 ratio is found to be higher during December-February and lower during March- September with a rise in August, which indicates the effect of 3 mechanisms: i) dilution effect of wind speed on PM2.5 during December-February, ii) re-suspension effect of wind speed on PM10 during March-September and iii) more pronounced scavenging effect of rainfall on PM10 during August. The study indicates the need for properly accounting the influence of meteorology for better understanding of PM variation in urban areas in Bangladesh. Journal of Engineering Science 12(1), 2021, 1-8